2015
DOI: 10.1007/s00417-015-2968-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of psoriatic uveitis in Japanese patients

Abstract: Cases of psoriatic uveitis in Japan appear to present with acute non-granulomatous uveitis; other symptoms may include macular edema, retinal vasculitis, or hyperemic disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 24 publications
6
18
1
2
Order By: Relevance
“…Previous studies have shown that patients with uveitis associated with psoriasis usually exhibit acute non-granulomatous anterior uveitis, which is consistent with the findings for our current patient [6]. A recent large-scale study demonstrated that a group of patients with severe psoriasis who received systemic therapy had an increased risk of uveitis compared to patients with mild psoriasis who did not receive any systemic therapy [2].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that patients with uveitis associated with psoriasis usually exhibit acute non-granulomatous anterior uveitis, which is consistent with the findings for our current patient [6]. A recent large-scale study demonstrated that a group of patients with severe psoriasis who received systemic therapy had an increased risk of uveitis compared to patients with mild psoriasis who did not receive any systemic therapy [2].…”
Section: Discussionsupporting
confidence: 90%
“…Although it has been thought that posterior segment inflammation rarely occurs, several recent studies have reported finding posterior segment lesions [3, 4, 5]. Furthermore, about half of the patients become affected bilaterally several years after the original onset [6]. Tumor necrosis factor alpha (TNF-α) is an important inflammatory cytokine that is involved in various inflammatory diseases, including rheumatoid arthritis (RA), Crohn's disease, Behçet's disease, and psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In conclusion, erythrodermic psoriasis concomitant with uveitis is relatively rare, and it is essential to treat both the ocular inflammation and primary disease. 16 Treatment with biological agents should be recommended as a primary strategy for erythrodermic psoriasis with uveitis because of their rapid onset of action and achievement of long-term remission. The selection of biological agents for this condition remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injection of vancomycin as is done in some centers after cataract surgery has been rarely associated with retinal vasculitis 14 . Patients with birdshot chorioretinopathy 15 and uveitis in association with psoriasis 16 were also noted to have a predisposition to retinal vasculitis.…”
Section: Novel Insightsmentioning
confidence: 99%